2013
DOI: 10.1002/aqc.2361
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of mutual benefits of nest association among freshwater cyprinids and implications for conservation

Abstract: 1. Although nest association among Nocomis chubs and other minnows (Cyprinidae) is common throughout North America, the overall outcome of this relationship and its mechanisms of costs and benefits remain unclear. Because imperilment of stream fishes is affected by reproductive traits, the implications of this widespread interaction must be understood.2. Nest association mechanisms were explored using a multiple working hypotheses framework on fish assemblage data from 25 reaches in three tributaries of the Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 72 publications
1
33
0
Order By: Relevance
“…However, unlike other studies of Nocomis nesting substrate preference (Lobb & Orth 1988;Wisenden et al 2009), we found little evidence of substrate preference À most likely because we accounted for gape size. Accounting for the gape size of adult male chubs drastically reduced the large differences between Peoples et al (2013) observed respective average differences (adjacent minus preferred) of 25.1 and 131 mm (for hornyhead and river chub N. micropogon, respectively) but measured adjacent substrate particles up to 70 and 680 mm, respectively. Our study excluded pebbles greater than 40 mm.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, unlike other studies of Nocomis nesting substrate preference (Lobb & Orth 1988;Wisenden et al 2009), we found little evidence of substrate preference À most likely because we accounted for gape size. Accounting for the gape size of adult male chubs drastically reduced the large differences between Peoples et al (2013) observed respective average differences (adjacent minus preferred) of 25.1 and 131 mm (for hornyhead and river chub N. micropogon, respectively) but measured adjacent substrate particles up to 70 and 680 mm, respectively. Our study excluded pebbles greater than 40 mm.…”
Section: Discussionmentioning
confidence: 98%
“…Nest associate reproduction often is closely tied to that of Nocomis (Wallin 1992). This spawning mode greatly influences associate reproductive success (Peoples & Frimpong 2013), geographic distribution (Pendleton et al 2012), and dispersal processes (Walser et al 2000;Hitt & Roberts 2011). Thus, protection of Nocomis spawning habitat benefits numerous species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nest building fishes can facilitate associate reproduction through the unique physical characteristics of their nests and by providing parental care to broods (Vives 1990;Johnston 1994a). Accordingly, whether or not a species exhibits nest associative spawning (or lack thereof) can have important implications for persistence in changing environmental conditions (Hitt & Roberts 2011;Peoples & Frimpong 2013). Because these facilitative mechanisms are likely to differ among hosts and associates, a better understanding of the microhabitat characteristics of nests of various hosts is a logical starting point for understanding host switching in this system.…”
Section: Introductionmentioning
confidence: 99%
“…Over 30 cyprinid species have been documented using chub nests for spawning (Johnston & Page 1992). While the motive for other fish species using chub nests can vary and include egg predation, the spawning association of other species with Nocomis is widely considered mutualistic (Wallin 1992;Johnston 1994;Peoples & Frimpong 2013), making the chubs likely keystone species. The male chub cleans, guards, and buries the eggs against predators, thereby enhancing hatching success.…”
Section: Introductionmentioning
confidence: 99%